Recent Advances in Magnetic Feˣ⁺/TiO₂ Microfibers for Wastewater Treatment as Climate Change Mitigation - Misriyani Misriyani; Yang Tian; Z. Ryan Tian (Jurnal Kimia Sains dan Aplikasi, 2024)
Chemical dyeing and finishing processes used in the clothing and textile industries are among the main contributors that can increase the impact of climate change. Photocatalysis using nanosized titanium dioxide (TiO2) has been continuously developed as a promising technology for purifying dye wastewater into simpler and environmentally friendly components. In addition, the decoration of iron cations (Fe2+) and (Fe3+) increases the reusability of the photocatalyst due to their magnetic properties, which are easy to collect for the recycling process. Magnetic Fex+/TiO2 microfibers have been successfully prepared using a hydrothermal method using titanium dioxide in an alkaline solution. Cations were added into the solution with the different molar ratios of Ti/Fex+ to produce Fe2+/TNW and Fe3+/TNW, respectively. Photocatalysis activity test using magnetic Fex+/TNW was carried out using methylene blue in a reactor equipped with an incandescent bulb lamp representing solar light. The results showed that adding the cations resulted in a new shape of palm tree leaves, like titanate microfibers. Controlling the cation’s molar ratio produces the magnetic Fex+/TNW with a 50-150 µm length. SEM images of each material presented the uniformly elongated shape and aggregated on one side morphology. In addition, paramagnetic properties indicate that magnetic Fex+/TNW can be easily separated from the dispersion in less than 1 minute using an external magnet. A photocatalysis activity test of magnetic Fex+/TNW was performed by calculating the percent degradation of methylene blue with variations in irradiation time in visible light conditions. The result showed the effectiveness of photodegradation of methylene blue was significantly increased in materials with 3.3 molar ratios of both Ti/Fe2+ and Ti/Fe3+ with a percent degradation reaching 79% and 70%, respectively, in 5 hours. In conclusion, magnetic Fex+/TNW is introduced as an alternative dye wastewater treatment technology that has reusable properties and works well on sustainable energy sources of solar light.